Local government communication in Indonesia: observations from Banjarmasin, South Kalimantan - Akhmad, Bachruddin Ali (Penerbit Universiti Kebangsaan Malaysia, 2020)
Most studies of democratization in developing countries fail to link their analysis with the implementation of local government communication. As a consequence, the study of government communication is too elitist and central government-oriented. This study contributes to the study of government communication in the context of local governance for countries in a democratic transition. The authors use local government communication in public services in Banjarmasin City, South Kalimantan Province, Indonesia, as a case of observation. Using a qualitative approach to explore the complexity of cultural and structural factors, the authors combine the results of an analysis of various documents, observations and in-depth interviews relating to the practices of local government communication in South Kalimantan from January to June 2018. In conclusion, the results indicated that the quality of local government communication was influenced by various factors both cultural and structural. Although local cultural factors remain important, in the case of the South Kalimantan, structural factors have more influence on regional government communication. While regional government communication performance does not yet involve active participation from below, more elite-oriented than public-oriented. The regional government officers are less responsive and still topdown, so the ideas of professionalization of local government communications are still limited to expectations rather than reality. This study recommends that local government communication can be effective if it adopts a participatory government communication perspective by involving the key stakeholders and local people in participation in the planning and implementation of communication including women's voices and perspectives.